2002
DOI: 10.1016/s0142-9612(01)00211-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of collagen sponge incorporating transforming growth factor-β1 to promote bone repair in skull defects in rabbits

Abstract: The objective of this study was to evaluate the potential of collagen sponge incorporating transforming growth factor-beta1 (TGF-beta1) to enhance bone repair. The collagen sponge was prepared by freeze-drying aqueous foamed collagen solution. Thermal cross-linking was performed in a vacuum at 140 degrees C for periods ranging from 1 to 48 h to prepare a number of fine collagen sponges. When collagen sponges incorporating 125I-labeled TGF-beta1 were placed in phosphate-buffered saline (PBS) solution at 37 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 22 publications
1
71
1
1
Order By: Relevance
“…The majority of IGF-1 release (26%-44% of the loaded IGF-1) occurred in a rapid burst release up to 24 h. This was followed by a slow controlled release in which a further 13%-16% was released between days 1 and 14. Many studies have reported similar burst releases of growth factor from such delivery devices occurring within the first 24 h. 45,[51][52][53][54] For example, Ueda et al reported that *30% of transforming growth factor-b1 incorporated in a collagen scaffold was released into the PBS by simple diffusion within the first hour of an in vitro release test. 53 We found that the percent of IGF-1 released after 24 h depended on the initial IGF-1 loading concentration and that therefore reducing the volume or loading concentration of IGF-1 could be used to reduce the burst release from this system.…”
Section: Elution Of Igf-1mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of IGF-1 release (26%-44% of the loaded IGF-1) occurred in a rapid burst release up to 24 h. This was followed by a slow controlled release in which a further 13%-16% was released between days 1 and 14. Many studies have reported similar burst releases of growth factor from such delivery devices occurring within the first 24 h. 45,[51][52][53][54] For example, Ueda et al reported that *30% of transforming growth factor-b1 incorporated in a collagen scaffold was released into the PBS by simple diffusion within the first hour of an in vitro release test. 53 We found that the percent of IGF-1 released after 24 h depended on the initial IGF-1 loading concentration and that therefore reducing the volume or loading concentration of IGF-1 could be used to reduce the burst release from this system.…”
Section: Elution Of Igf-1mentioning
confidence: 99%
“…Our results demonstrated that DHT had no significant effect on the adsorption or release of IGF-1 from our scaffolds, and this may add weight to the hypothesis that IGF-1 binding is influenced by the presence of CS rather than collagen in the scaffold 47,50,56 Previous studies demonstrated that increasing the length of DHT treatment had no effect on transforming growth factor-b1 release from a collagen scaffold, but scaffolds cross-linked without DHT were not compared. 53 Our future studies will study collagen scaffolds containing different proportions of GAG to establish the role of GAGs in growth factor binding in this type of scaffold. IGF-1, insulin-like growth factor-1.…”
Section: Elution Of Igf-1mentioning
confidence: 99%
“…However, the degradation rates of other polymers cannot be tailored within such a high range as that of silk. Collagen degrades between 1 to 4 weeks and sometimes longer depending on the cross-linking process [129], whereas. PCL can last within the body for more than 2 years [130].…”
Section: Electrospinning Silk Fibroinmentioning
confidence: 99%
“…Most experimental interest is in transforming growth factor (TGF) beta (mainly 1 and 3), a potent chondrogenic with osteoinductive properties [54], and bone morphogenetic protein (BMP) (mainly 2 and 7), a potent osteogenic but which aids in chondral and osseous proliferation and differentiation [14]. BMP-7 (Osteo Progenitor-1; OP-1) was found to be a potent osteogenic factor in the treatment of tibial fracture non-union [14].…”
Section: Future Trends/researchmentioning
confidence: 99%